The Effect of Health Education through Family Centered Care on the Motivation and Behavior of Tuberculosis Patients in Tuberculosis Recovery - Petrus Belarminus; Shelfi Dwi Retnani Putri Santoso; Dessy Natalia Riti (Babali Nursing Research, 2023)
Introduction: Tuberculosis (TB) is an infectious disease that continues to be a global concern and health issues. Based on the findings of the National Riskesdas in 2018, the prevalence was 1,017,290 cases of pulmonary TB, 20,599 cases in NTT, and 1066 TB cases in West Sumba Regency. Family involvement will contribute to better TB case management. This research aims to determine the effect of health education based on family- centered care on the motivation and behavior of Tubercolosis patients in Tubercolosis Recovery in West Sumba Regency. Method: This research is a Quasi experiment with one group pre and post test with control group design. The sampling technique used was consecutive sampling. The total of 40 respondents. Results: Based on the results of the independent t-test statistical test for the pre-test, the motivation value showed a value of p = 0.228, and the post-test showed a value of p = 0.749. The results of the paired t-test statistical test in the treatment group have a value of p = 0.000, in the control group the value of p = 0.011. The statistical results of the Wilcoxon test before and after the intervention in the treatment group were p= 0.000, while in the control group showed p= 0.180. Conclusion: Health education through family-centered care can be used as an approach to boost motivation and Adherence of TB patients in taking their medication. Family support is a significant factor in encouraging patients to comply their TB treatment.